2009
DOI: 10.1007/s00384-009-0662-x
|View full text |Cite
|
Sign up to set email alerts
|

Loop ileostomy versus loop colostomy for fecal diversion after colorectal or coloanal anastomosis: a meta-analysis

Abstract: Our overview shows that LI is associated with a lower risk of construction of the stoma outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
2
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(97 citation statements)
references
References 25 publications
2
82
2
11
Order By: Relevance
“…Sus consecuencias pueden reducirse con la construcció n de una colostomía o una ileostomía derivativa temporal (IDT) 1,2 , siendo preferible esta ú ltima por su asociació n a un menor riesgo de complicaciones [3][4][5][6] .…”
Section: Introducció Nunclassified
“…Sus consecuencias pueden reducirse con la construcció n de una colostomía o una ileostomía derivativa temporal (IDT) 1,2 , siendo preferible esta ú ltima por su asociació n a un menor riesgo de complicaciones [3][4][5][6] .…”
Section: Introducció Nunclassified
“…Ob neuere Verfahren wie die Plug-Implantation diese aufwendigen Rekonstruktionen verdrängen, bleibt abzuwarten[31]. Trotz kontroverser Diskussionen erscheint aus unserer Sicht die Anlage eines protektiven Enterostomas unerlässlich[32,33]. Das Fehlen der Stuhlsäule und der Drucksteigerung im Defäkations-vorgang erscheinen hier als wesentlichste die Wundheilung för-dernde Maßnahme.…”
unclassified
“…A meta-analysis in 2009 concluded that stoma closure results in additional morbidity for 17% of patients, a 3.7% reoperation rate and 0.4% mortality rate. 22 Furthermore, prior to reversal, stomas have been associated with complications like dermatitis, parastomal hernia, stenosis, hemorrhage, prolapse, retraction and dehydration in up to 60% of patients, 12,[23][24][25] and the incidence increases with the duration of the stoma. 12 Therefore, we sought to further characterize factors associated with non-reversal and delayed reversal among elderly patients, those most at risk for non-reversal, to aid in pre-operative counseling and realistic expectation setting.…”
Section: Discussionmentioning
confidence: 99%